Trend Sentimen Pemilih Berbasis Kedaerahan Pada Pilgub 2017 Di Babel - RANTO M.A. (Politii : Jurnal Politik, Demokrasi, HAM, Lingkungan, Maritim dan SDA, 2017)
Based on the gubernatorial elections of Bangka Belitung Islands Province in 2007,2012, and 2017 that it has some primordial aspects played a role running local democratic mechanism. Due to the aspects it is important to track people choice trend which is related to primordial sentiment concideration in choosing their political interests. This paper also discussed about voters responses in determining their political interests based on primordial sentiment aspects in gubernatorial election 2017. This research used public opinion survey where the respondents was selected randomly with multistage random sampling procedure. Data was analyzed using statistic descriptive analysis method by showing frequency graphic to explain localized sentimental dynamics in Bangka Belitung. The research showed that the primordial sentiment trend has still become concideration and it is around 65,5% of voters in Bangka Belitung choosed by concidering the primordial sentiment. The comparison between voters in Bangka and in Belitung can be concluded that voters in Belitung are more sentiment in concidering their political candidates which tend to vote local man than voters in Bangka. Keywords: Election, Primordial